Elucidating the role of fat-inducing transmembrane protein 2 (Fit2) in insulin-producing beta-cells (β-cells) - Koh, Tracy (2015)
Fat-Inducing Transmembrane protein 2 (Fit2/Fitm2) is an evolutionarily conserved transmembrane protein. Located on the membrane of the endoplasmic reticulum(ER), Fit2 has been shown to play an important role [1] in the packaging of triglycerides into lipid droplets(LD) within adipocytes (Fig.1). Pancreatic beta-cells (β-cells) secrete insulin. In diabetes β-cell dysfunction is driven partly by lipid stress (lipotoxicity). Fit2 is expressed in β-cells but its function remains elusive. [2nd Award]